THE TYPOLOGIES OF THE HOUSES IN THE MEDINA OF ANNABA-ALGERIA - Labbaci Ines; Attoui Redha (International Journal of Innovative Technologies in Social Science, 2024)
The patio house is a cultural production, it bears witness to the social practices of ancient societies that shaped its spaces by considering their own cultures and needs, this is how it was born and developed into a spontaneous architecture consistent with the environment, the prevailing climate, the culture and interests of the family and its future generations, For years, the Annaba Medina had suffered from the precariousness of unhealthy, over-densified housing. The original families were leaving and lowincome rural immigrants were finding the Medina a favorable host structure, with large empty mansions and a type of house with patios that lent itself to renting by the piece. The unsuitability of this urban fabric for the current standards and practices of the inhabitants, and contemporary development, were the main causes of the changes made by the Medinese throughout the area, mainly affecting the original urban form. Through this research, we have tried to analyze the traditional domestic space to highlight the new typologies of houses in Medina.